Carbon Emission Limit Policy In Indonesia - Ilham Pribadi; Hanna Resika; Jessica Aquera (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Global warming has become a significant issue faced by all countries worldwide. One of the main causes of global warming is the excessive emission of carbon resulting from human activities. Governments play a crucial role in limiting carbon footprints, as reducing carbon emissions can significantly impact national economic activities. Indonesia has demonstrated its commitment to mitigating global warming by ratifying the Paris Agreement. The country has also implemented a Carbon Economic Value (CEV) policy. This policy aims to reduce carbon emissions and encourage green investment. This study aims to examine government policies in reducing carbon footprints in Indonesia.